XML for DB2 information integration - Steegmans, Bart (IBM redbooks., 2004)
In many organizations, relational databases are the backbone for data storage and retrieval. Over the last couple of years, XML has become the de facto standard to exchange information between organizations, as well as between departments or applications within the same organization. Since data tends to live in databases, it needs to be converted from a relational format into an XML format when involved in those data exchanges, as well as converted (back) from XML into a relational format for storage, or for handling by other applications. How can we achieve this? This IBM Redbooks publication describes how to design the mapping between XML and relational data, and vice versa, to enable a flexible exchange of information. IBM provides a number of products to help you bridge the gap between XML and its relational database, DB2. The DB2 engine itself provides support to generate XML fragments from relational data through the use of SQL/XML built-in functions. DB2 also provides the DB2 XML Extender. It allows you to perform XML composition, like SQL/XML, but also provides functionality to decompose XML documents and store XML documents intact inside the database. XML Extender also provides a set of transformation and validation functions. Another option to work with XML is to use the XML wrapper, a part of the set of non-relational wrappers of DB2 Information Integrator. This book also looks at the IBM tools available to assist you when dealing with XML, specifically WebSphere Application Developer and DB2 Control Center. To add a more practical angle, these functions and products are illustrated through the development of a simple application.